A Walk in Customers' Shoes: How Attentional Bias Modification Affects Ownership of Integrity-violating Social Media Posts. Issue 1 (February 2013) - van Laer, Tom; de Ruyter, Ko; Cox, David
The number of social media posts that expose company integrity violations has increased dramatically. In response, some companies empower employees to respond to customer blogs, which requires employees to recognize the customer's perspective. We show that attentional bias modification can be used to prime employees of two global Fortune 100 companies with a self-sufficiency or empathy bias. The results indicate that narrative transportation, or the extent to which employees mentally enter the world evoked by a customer's story, mediates the effect of attentional bias on two relevant psychological ownership dimensions: acknowledgment of responsibility and willingness to respond. Participants with a self-sufficiency bias neither acknowledge responsibility nor want to respond. However, participants primed with an empathy bias take responsibility for the customer's case and respond to the integrity violation. We find evidence for two boundary conditions of this effect: (1) it strengthens when the employee perceives the customer's financial vulnerability as high and (2) it weakens when the customer is impolite in the blog post.